Group portrait of students at College of the Pacific on Arbor Day - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of students, posing in front of a building and on the second floor balcony above. The building is probably the Helen Gunth Hall, built in 1909. Ownership transferred in 1925 to Bellermine Preperatory School, and demolished in 1997. To the left of the crowd is a group of older adults and some children. The building in the background is possibly the Helen Gunth Hall.